Peripheral neuropathy in patients with hepatitis virus C infection in the Amazon region - Irenio Gomes; Daniel Bocchese Nora; Nelson Cezar Marquezini; Gerard Said; Ailton Melo (Arquivos de Neuro-Psiquiatria)
INTRODUCTION: Hepatitis virus C (HCV) infection is considered a health problem in the State of Acre localized in the Brazilian Amazon which has a prevalence rate of 5.9%. Peripheral neuropathy is a common extra-hepatic manifestation in patients with HCV. OBJECTIVE: To determine the prevalence of peripheral neuropathies using clinical and neurophysiological parameters. METHOD: A cross sectional study was performed in patients assisted by a specialized center of infectious diseases in the State of Acre. All patients completed a clinicoepidemiological questionnaire, physical examination and nerve conduction studies (NCS). RESULTS: We studied 78 patients with mean age 45.5 years (range from 10 to 76 years), two thirds were male, 51% had at least 8 years of formal education and 96% lived in the capital city of Acre State. Roughly 34% of patients complained about paresthesias mainly in upper limbs. The NCS diagnosed multiple mononeuropathy in 11 (14.1%; IC95% 7.6-23.2) patients and carpal tunnel syndrome in 4 (5.1%) patients. CONCLUSION: Subclinical involvement of peripheral nerves seems common in patients with HCV, with multiple mononeuropathy the main manifestation of nerve injury in this region as suggested by electrophysiological studies.